Singapore Management University Report to Stakeholders 2010 - 2011 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2010)
The past year has been one of transition for SMU. We celebrated the University’s first ten successful years and looked forward to our second. I bade farewell to Professor Howard Hunter our previous president and to Dr Richard Hu our previous chancellor, as I welcomed Professor Arnoud De Meyer and Mr Yong Pung How into these offices. More recently, we held our last Patron’s Day with Singapore’s former President S.R. Nathan as Patron, and I look forward to greeting President Tony Tan as our new Patron. It has also been a year in which we left behind the role of being a new university finding our place in the local educational landscape and the University leadership has been engaged in determining our strategic goals for the next decade. These goals require us to set out on a journey to make our mark in the region and around the world. As part of this, we are dedicating a far greater proportion of our resources to research.